The Business of Dermatology - Dover, Jeffrey S. (Thieme Medical Publishers, Incorporated, 2020)
The ultimate guide to managing the multifaceted business aspects of a dermatology practice Although board-certified dermatologists provide the best care for their patients, managing a practice and optimizing every facet of the business is a daunting endeavor. Business acumen is not taught in residency and is the most overlooked aspect of any given practice. The Business of Dermatology, written by esteemed dermatologists Jeffrey S. Dover, Kavita Mariwalla, and an impressive group of experts, provides a rare opportunity to learn about the operations side of practices across the country. Written.